MEASUREMENT OF WORKING TIME IN THE PRODUCTION PROCESS Ã¢â‚¬ÂKERUPUK IKANÃ¢â‚¬ÂIN GRESIK HOME INDUSTRY: MEASUREMENT OF WORKING TIME IN THE PRODUCTION PROCESS Ã¢â‚¬ÂKERUPUK IKANÃ¢â‚¬ÂIN GRESIK HOME INDUSTRY - Utomo, Yitno (Tibuana, 2018)
Measurement of time in the production process is necessary to know the length of time on each steps of making fish crackers. The timing is done directly using a stopwatch tool, with the aim of knowing the normal time, standard time, and cycle time as an improvement of production process time. In this study using descriptive method, which is one research method that describes the place of the process of production of fish crackers as appropriate. The result shows the time required in one production process is normal time 3986,12 minutes, standard time 4113,84 minutes, and cycle time get 2657,02 minutes.